Electrical Properties of Textured Niobium-Doped Bismuth Titanate Ceramics - Aguiar, Ederson C. [UNESP]; Simões, Alexandre Zirpoli [UNESP]; Foschini, Cesar R. [UNESP]; Perazolli, Leinig A. [UNESP]; Mistler, Richard E.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Wiley-Blackwell, 2012)
Crystallographically textured Nb-doped bismuth titanate ceramics Bi4Ti(3-x)NbxO12, were fabricated by tape casting using plate-like Bi4Ti3O12 particles prepared by a molten-salt method as the templates. The templates were aligned in the fine-grained matrix by aqueous tape casting with their major surface parallel to the casting plane. Effect of niobium on the grain orientation in the material was investigated. It was found that the use of a fine precursor powder led to enhanced densification of the ceramic, while Nb doping reduced electrical conduction and dielectric loss, which enabled poling at high temperatures and high electric fields. The textured Bi4Ti3O12 ceramic showed a high anisotropy in its dielectric properties in the directions parallel and perpendicular to the casting plane. Highly textured BiT was obtained with the use of only 5 similar to wt% of template particles by sintering at 800 degrees C for 1 similar to h.